Konten Instagram Unilever Indonesia Sebagai Upaya Branding Ramah Lingkungan - Maya May Syarah; Sri Wulandari (Brand Communication, 2022)
Abstract: Unilever is considered environmentally friendly, doing digital branding to strengthen the company's image for a positive image. The digital branding tool is Instagram social media with the @unileveridn account. Instagram was chosen because as a social media it allows various forms of sharing, collaboration, and mutual understanding both in writing, visually, and audiovisually. Environmentally friendly content is used to describe activities that are good for the environment. Use qualitative descriptive methodology with a case study approach, this study aims to determine the content on Unilever Instagram as an environmentally friendly company branding effort. The results of the study stated that digital branding through content uploaded to @unileveridn aims as a media campaign or education related to the environment, including the use of sustainable resources, preservation of environmental functions. Environmentally friendly products such as products that can be recycled, reduce pollution, and conserve energy. It @unileveridn is considered effective in building a brand as an environmentally friendly company, this can also improve two-way communication with the wider community, as seen from the responses in the form of likes, comments and views. In delivering content, we sometimes collaborate with communities or institutions that care about the environment. This is in accordance with the functions of social media, namely Sharing, Collaborating and Connecting.